Asymmetric Bioreduction of β‐Activated Vinylphosphonate Derivatives Using Ene‐Reductases. Issue 23 (18th October 2017) - Janicki, Ignacy; Kiełbasiński, Piotr; Turrini, Nikolaus G.; Faber, Kurt; Hall, Mélanie
Abstract: A series of functionalized α‐chiral phosphonates was obtained by enzymatic reduction of the corresponding β‐activated vinylphosphonate derivatives employing several ene‐reductases of the Old Yellow Enzyme family as biocatalysts. The insufficient activation of the phosphonate group alone was compensated by introduction of an electron‐withdrawing group at the β‐position, which resulted in high levels of conversion (up to >99%). All active enzymes consistently furnished ( R )‐configurated products with exquisite stereoselectivity, thereby providing a stereo‐complementary approach to current asymmetric hydrogenation protocols on similar compounds. Preparative‐scale syntheses performed in aqueous buffer using formate/formate dehydrogenase for recycling of the nicotinamide cofactor granted access to β‐keto‐, cyano‐ and ester phosphonates from the ( E )‐isomers of α, β‐unsaturated phosphonates in up to 72% isolated yield and >99% ee . Abstract :